Pembelajaran Berbasis Laboratorium IPA untuk Melatih Keterampilan Komunikasi Ilmiah Siswa SMP Kelas VII - Ika, Yasinta Embu (Universitas Nurul Huda, 2018)
This research aims to produce teaching materials based on science laboratory which is valid, practical, and effective to facilitate the students’ scientific communication skill. The development of teaching material used the R&D model and was implemented in 7th grade of SMP Negeri 1 Ende in the second semester of 2017/2018 by using the Pre-Experimental One-Group Pretest-Posttest Design. The data collection used documentation, observation, test, and quetionnaires. The data analysis techniques used quantitative and qualitative descriptive analysis. The results of this research are:1) Teaching material developed is valid to be used. It consists of Syllabus, Lesson Plan, Student Worksheet and Test of student learning outcomes; 2) The practicality of teaching material is categorized into feasible according to lesson plan implementation, students give a positive responses toward teaching material and the implementation of teaching material; and 3) The teaching material is effective in terms of: (a) Improvement of students’ learning achievement; (b) Improvement of students’ scientific communication skill. Thus, the teaching materials based on science laboratory are valid, practical, and effective to facilitate the students’ scientific communication skill.